Rapid generation of volatile fatty acids (VFA) through anaerobic acidification of livestock organic waste at low hydraulic residence time (HRT). (August 2017) - Kuruti, Kranti; Nakkasunchi, Shalini; Begum, Sameena; Juntupally, Sudharshan; Arelli, Vijayalakshmi; Anupoju, Gangagni Rao
Graphical abstract: Acidogenic anaerobic digestion of livestock organic waste for the production of volatile fatty acids at low hydraulic residence time (HRT). Highlights: Rapid generation of VFA's through acidogenic anaerobic digestion from CM and PL. Pre-treatment of CM and PL, optimization of pH, HRT and F/M ratio to maximize VFAs. HRT of 4 days, pH of 5.5, and F/M ratio of 1.0 were found optimum for the process. Pre-treated CM and PL yielded 0.43 and 0.67 kg of VFA/(kg VS reduced) respectively. Abstract: The purpose of this study was to investigate the effect of pre-treatment and F/M (Food to Microorganism) ratios for the rapid generation of volatile fatty acids (VFA) from livestock organic wastes (cattle manure (CM) and poultry litter (PL)) through an anaerobic acidification process at a pH range of 4.5–5.5. Experiments were organized using CM and PL in batch reactors (1 L and 25 L) with and with no pre-treatment of substrate at F/M ratios (0.4, 0.6, 0.8 and 1). Among various existing pre-treatments methods, thermal-acidic (120 °C; 1% H2 SO4 ) pre-treatment was found effective. The results revealed that 0.31 and 0.47 kg VFA/(kg VS reduced) could be obtained from CM and PL respectively with no pre-treatment, whereas it improvised to 0.43 and 0.67 kg VFA/(kg VS reduced) correspondingly due to pre-treatment. Aforesaid, better yield of VFA was obtained at F/M ratio of 1.0, pH-5.5 and hydraulic residence time of 4 days.